The Analysis of Influence of Work Discipline and Organizational Culture on the Performance of State Civil Apparatus - Sri Purwati; Ana Fitriyatul Bilgies; Ghalib Suprianto; Mariani; Muhammad Amsal Nasution (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
This study intends to identify and investigate how organizational culture and work ethics affect the effectiveness of the civil apparatus (PNS). 65 government workers participated in this study utilizing the saturated sample methodology as the sample size. The SPSS 17.0 program was used to collect data through the distribution of questionnaires and library data, which was then analyzed using multiple linear regression analysis methods. According to the analysis that has been done, the findings of this study show that organizational culture and work discipline have a significant impact on the performance of civil servants (PNS), both partially and simultaneously. In fact, 47% of employee performance can be attributed to organizational culture and work discipline.